2008
DOI: 10.1002/mame.200800081
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Polymer/Clay Nanocomposites: Effect of Clay Size on the Structure of Multilayered Films

Abstract: The influence of size and surface area of two different types of clay on the structure and characteristics of PEO/clay nanocomposites in the form of multilayered films is discussed. To search for new synergistic properties and/or improve the properties of nanocomposite films already known, we study polymer nanocomposites that have laponite as well as montmorillonite incorporated. While DSC measurements showed that higher laponite amounts gradually suppress the crystallinity of PEO in the nanocomposite, XRD mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…With addition of salt, the electrostatic adhesion in the material plays an important role in welding the nanostructures together. Similar to that which has been observed for different polymer/clay systems, 59 XRD measurements on our laponite/PEO films indicated that the polymer chains intercalate the clay platelets regardless of the salt addition. The conditions for film preparation were selected to assure that the shear rate and intermediate film thicknesses were not critical to the final film structure.…”
Section: Resultssupporting
confidence: 89%
“…With addition of salt, the electrostatic adhesion in the material plays an important role in welding the nanostructures together. Similar to that which has been observed for different polymer/clay systems, 59 XRD measurements on our laponite/PEO films indicated that the polymer chains intercalate the clay platelets regardless of the salt addition. The conditions for film preparation were selected to assure that the shear rate and intermediate film thicknesses were not critical to the final film structure.…”
Section: Resultssupporting
confidence: 89%
“…The d ‐spacing values of the pure montmorillonite are around 11.5 Å. The difference in the d ‐spacing between polymer nanocomposites and pure clay (approximately 6 Å) is attributed to the presence of PEO chains between the clay platelets 50. Overall, SAXS and XRD measurements indicate that, at the nanoscale, the clay platelets orient parallel to the film plane and intercalate the polymer chains regardless of the type of salt incorporated in the nanocomposite film.…”
Section: Resultssupporting
confidence: 83%
“…Novel physical properties of soft and bulk polymer nanocomposite materials are also dependent on the supramolecular organization of the nanostructures [ 5 ]. The presence of the nanoparticle and the interaction of the polymer with the particle, as well as the particle orientation in a dispersed fluid composition may lead to a variety of ordered composite materials in the bulk or film [ 6 , 7 , 8 ]. Incorporation of metals into polymer matrixes has been shown to produce unique optical, magnetic and dielectric properties at the nano- and macro-scale in nanocomposites, apparently due to the surface and confinement effects of the nanoparticles [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introduction To Polymer Nanocompositesmentioning
confidence: 99%
“…In aqueous solutions and gels hydrophilic polymers strongly adsorb to the charged Laponite ® nanoparticles leading to the formation of transparent systems. Smectites such as montmorillonite are 2:1 charged phyllosilicates that contain exchangeable interlayer cations and show the ability to intercalate various polymers [ 6 ]. Montmorillonite clay produces an opaque suspension of predominantly exfoliated platelets that range on average in size from ca.…”
Section: Introduction To Polymer Nanocompositesmentioning
confidence: 99%